Analysis of the Application of Agrarian and Spatial Planning Laws in Land Disputes for the Development of Public Facilities - Muhammad Ukasyah; Karina Putri (Enigma Institute, 2023)
The Agrarian and Spatial Planning Law (UUATR) is used to settle land disputes so that public facilities can be built. It is a legal process that tries to find a balance between land owners' rights and the needs of the community and the government's desire to build infrastructure that helps the economy grow. UUATR is an important legal framework for regulating land rights, ownership, and procedures that must be followed in resolving land disputes. In land disputes for the construction of public facilities, the application of the agrarian law plays an important role in maintaining a balance between public interests in infrastructure development and the rights of land owners. The application of the agrarian law in land disputes for the construction of public facilities ensures that important infrastructure development can proceed in line with the public interest while safeguarding the rights and welfare of land owners. This creates a fair and sustainable framework for resolving land disputes in Indonesia.